A Study of The Quality of Life in Patients with Schizophrenia: A Cross-Sectional Study in A Tertiary Care Hospital, Mumbai, India - Prasad Tagad; Nitin Bhoge; Ivan Netto; Pritish Raut (Medsci Publications, 2024)
Background: There are limited recent Indian studies assessing the quality of life in patients with schizophrenia. This study evaluated the socio-demographic data, psychopathology, quality of life, and their associations in patients with schizophrenia. Methodology: Fifty outpatients with schizophrenia, meeting ICD-10 DCR criteria, were assessed using Kuppuswamy's socioeconomic status scale, the Positive and Negative Syndrome Scale (PANSS), and the Quality-of-Life Scale (QLS). Results: The mean patient age was 36.3 years, with a male-to-female ratio of 1.6:1. Most patients were married, unemployed, educated up to middle school, and belonged to the upper-lower socioeconomic class. Clinically, they had mild psychopathology with a mean PANSS total score of 62.36. Quality of life assessment revealed that 12% had severe impairment, 64% had mild to moderate impairment, and 24% had no impairment. Occupational status was significantly associated with QLS scores. PANSS scores negatively correlated with QLS scores, with stronger correlations in the general psychopathology and negative symptom domains. Conclusion: The findings emphasize the need for personalized and holistic approaches to managing schizophrenia, addressing both clinical symptoms and socio-demographic challenges.